+0  
 
0
77
1
avatar

Define \(g\) by \(g(x)=5x-4\). If \(g(x)=f^{-1}(x)-3\) and \(f^{-1}(x)\) is the inverse of the function \(f(x)=ax+b\), find \(5a+5b\).

 Mar 2, 2020
 #1
avatar+111438 
+1

f(x) =  ax  + b

y = ax  + b               get x by itself

y - b  = ax

[y -b ] / a  = x         "swap"  x  and  y

[x - b ]  / a = y    =  f-1(x)

 

So

 

f-1(x)  - 3   =    g (x)

 

[ x - b ]  /  a   -  3 =   5x  - 4         add 3 to both sides

 

[ x - b ] / a  =  5x    -  1           simplify 

 

(1/a)x  -  b/a   =  5x   - 1

 

Equating  terms

 

(1/a)  =  5    ⇒   5a  = 1   ⇒    a  = 1/5

 

And 

 

b/a =  1

 

b /(1/5)   = 1

 

b  = 1 * (1/5)

 

b = 1/5

 

So

 

5a  +  5b   =

 

5(1/5)  + 5 (1/5)   =

 

1  +   1     =

 

2

 

 

 

cool cool cool

 Mar 2, 2020

10 Online Users